ЗИЁРАТ ТУРИЗМИНИНГ КИЧИК ҲУДУДЛАР ИҚТИСОДИЁТИДА ТУТГАН ЎРНИ ВА АҲАМИЯТИ - Қурбонов, Ш.Б.; Тўраев, Қ.Т.; Тўраева, З.М. (SCIENCE and SOCIETY, 2022)
The article tried to evaluate the role and importance of religious and pilgrimage tourism in the economy of small areas (towns where shrines are located) based on observations and sociological studies in a number of shrines in the republic. In particular, a chain scheme of the influence of religious and pilgrimage tourism on population employment has been developed, and proposals for the development of small and family entrepreneurship in settlements where places of pilgrimage are located based on the chain model have been put forward.
Keywords: tourism; pilgrim tourism; religious tourism; financial territories; cultural geography; objects of religious significance; regional economy